EVALUATING THE GLYCEMIC CONTROL INDEX OF CHRONIC KIDNEY DISEASE (CKD) PATIENTS IN SOKOTO - Otitolaiye, C. A.; Sahabi, D. M.; Makusidi, A. M.; Saidu, Y.; Bilbis, L. S. (FUDMA JOURNAL OF SCIENCES, 2023)
Diabetes is a clinical condition characterized by increased blood glucose level (hyperglycemia). Prolonged diabetes is life threatening and is one of the major risk factors of CKD. If not properly monitored could predispose an individual to a high risk of cardiovascular complication and hasten the progression of CKD to attain end stage renal disease (ESRD). As such the maintenance of glucose homeostasis is crucial in preventing pathological consequences that may result from hyperglycemia. This study therefore aims to investigate the glycemic control index of CKD patients at each stage of the disease. This study was conducted on sixty seven CKD patients attending the nephrology units of Usmanu Danfodiyo University Teaching Hospital and Specialist Hospital Sokoto. The subjects weregrouped into stages based on their estimated glomerular filtration rate (eGFR) using the modification of diet in renal disease (MDRD) 4-variable equation. Blood samples were collected into lithium heparinised tubes and used to measure the glucose, glycated hemoglobin (HbA1c) and creatinine levels. The glucose level decreased from stage 1 (p > 0.05) to stage 5 while the HbA1c significantly increased as CKD advances. The HbA1c showed a highly significant negative correlation with eGFR (p = 0.0002). This study has shown there is poor glycemic control even in normoglycemic condition which could increase their progression to end stage renal disease (ESRD) and worsen the morbidity/ mortality rate among the CKD patients.